“It’s Not the Same as School”: Online Learning During COVID-19 for Families Facing Socially Disadvantaging Circumstances and the Role of a Community Organization - Campbell, Sydney; Wang, Ruo Lan; Carnevale, Franco A. (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Based on the transition to online learning during the COVID-19 pandemic, we studied the experiences of families and children facing socially disadvantaging circumstances in Montréal in navigating this novel learning environment, with a focus on community organization supports. These families faced pronounced difficulties adapting to online learning due to disorganized communication with schools, unexpected shifts in parents’ roles, and resource constraints. However, the community organization was instrumental in supporting families and promoting a sense of agency in children. Policymakers ought to prioritize investment in community organizations that target educational supports to prevent/reduce adverse outcomes associated with pandemics or other public health emergencies.